2020
DOI: 10.2224/sbp.9330
|View full text |Cite
|
Sign up to set email alerts
|

Leader narcissism and subordinate change-oriented organizational citizenship behavior: Overall justice as a moderator

Abstract: We examined the effect of leader narcissism on the change-oriented organizational citizenship behavior of subordinates and the mediating role of leader–member exchange (LMX) in this relationship. We further proposed that perceived overall justice would moderate the relationship between leader narcissism and LMX. We used data from 158 pairs of squadron leaders and subordinates in 4 battalions of the Korean Army. Hierarchical regression analysis results confirmed the proposed effects and further revealed a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…On the other hand, Lang et al ( 2022) concluded that organizational narcissism has a positive effect on change-oriented OCB and that this relationship is more pronounced in uncertain environments. Similarly, Ha, Lee, Byun, and Dai (2020) found that leader narcissism has a positive effect on subordinates' change-oriented OCB. However, a different study also reveals that leader narcissism has a negative effect on employees' leader-oriented OCB (Wang et al, 2021).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 88%
“…On the other hand, Lang et al ( 2022) concluded that organizational narcissism has a positive effect on change-oriented OCB and that this relationship is more pronounced in uncertain environments. Similarly, Ha, Lee, Byun, and Dai (2020) found that leader narcissism has a positive effect on subordinates' change-oriented OCB. However, a different study also reveals that leader narcissism has a negative effect on employees' leader-oriented OCB (Wang et al, 2021).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 88%
“…Initiating change is a visible way to demonstrate superiority. Narcissistic employees are thus willing to explore opportunities to advance the status quo ( Campbell et al, 2011 ; Ha et al, 2020 ). Prior research has found that narcissistic leaders present their followers with a vision of a future that is far superior to the status quo ( Ha et al, 2020 ).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Narcissistic employees are thus willing to explore opportunities to advance the status quo ( Campbell et al, 2011 ; Ha et al, 2020 ). Prior research has found that narcissistic leaders present their followers with a vision of a future that is far superior to the status quo ( Ha et al, 2020 ). In a similar vein, we propose that narcissistic employees will be more motivated to take FRCC.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Given that leader narcissism has been shown to substantially impact employees ( O’Boyle et al, 2012 ), there is growing interest in identifying its specific effects. Prior studies have focused on the effects of leader narcissism on employees’ job performance ( Owens et al, 2015 ; Liu et al, 2021 ) and workplace behaviors such as voice behavior ( Liao et al, 2019b ; Huang et al, 2020 ; Yao et al, 2020 ), innovation behavior ( Yang et al, 2020 ; Norouzinik et al, 2021 ), change-oriented organizational citizenship behavior ( Ha et al, 2020 ), and counterproductive behavior ( O’Boyle et al, 2012 ; Braun et al, 2018 ). Although existing studies have provided valuable insights into the ways in which leader narcissism affects employees’ individual-directed and organization-directed behaviors, it does not answer the question of how leader narcissism affects employees’ leader-directed followership behavior.…”
Section: Introductionmentioning
confidence: 99%